Bottom-Up and Top-Down Attention Impairment Induced by Long-Term Exposure to Noise in the Absence of Threshold Shifts - Wang, Ying; Huang, Xuan; Zhang, Jiajia; Huang, Shujian; Wang, Jiping; Feng, Yanmei; Jiang, Zhuang; Wang, Hui; Yin, Shankai (Frontiers in Neurology, 2022)
Objective: We aimed to assess the effect of noise exposure on bottom-up and top-down attention functions in industrial workers based on behavioral and brain responses recorded by the multichannel electroencephalogram (EEG). Method: In this cross-sectional study, 563 shipyard noise-exposed workers with clinical normal hearing were recruited for cognitive testing. Personal cumulative noise exposure (CNE) was calculated with the long-term equivalent noise level and employment duration. The performance of cognitive tests was compared between the high CNE group (H-CNE, >92.2) and the low CNE group; additionally, brain responses were recorded with a 256-channel EEG from a subgroup of 20 noise-exposed (NG) workers, who were selected from the cohort with a pure tone threshold <25 dB HL from 0.25 to 16 kHz and 20 healthy controls matched for age, sex, and education. P300 and mismatch negativity (MMN) evoked by auditory stimuli were obtained to evaluate the top-down and bottom-up attention functions. The sources of P300 and MMN were investigated using GeoSource. Results: The total score of the cognitive test (24.55±3.71 vs. 25.32±2.62, p < 0.01) and the subscale of attention score (5.43±1.02 vs. 5.62±0.67, p < 0.001) were significantly lower in the H-CNE group than in the L-CNE group. The attention score has the fastest decline of all the cognitive domain dimensions (slope = -0.03 in individuals under 40 years old, p < 0.001; slope = -0.06 in individuals older than 40 years old, p < 0.001). When NG was compared to controls, the P300 amplitude was significantly decreased in NG at Cz (3.9±2.1μV vs. 6.7±2.3μV, p < 0.001). In addition, the latency of P300 (390.7±12.1ms vs. 369.4±7.5ms, p < 0.001) and MMN (172.8±15.5ms vs. 157.8±10.5ms, p < 0.01) was significantly prolonged in NG compared with controls. The source for MMN for controls was in the left BA11, whereas the noise exposure group's source was lateralized to the BA20. Conclusion: Long-term exposure to noise deteriorated the bottom-up and top-down attention functions even in the absence of threshold shifts, as evidenced by the behavioral and brain responses.